2023
DOI: 10.1093/ornithology/ukad023
|View full text |Cite
|
Sign up to set email alerts
|

Sixty-fourth Supplement to the American Ornithological Society’s Check-list of North American Birds

Abstract: The following changes to the 7th edition (page numbers refer thereto) and its supplements result from the Committee's actions:pp. xvii-liv. Increase the number in the title of the list of species to 2,186. Insert the following names in the proper position as indicated by the text of this supplement: FlorisuginaeAntrostomus cubanensis Cuban Nightjar. Antrostomus ekmani Hispaniolan Nightjar. Mustelirallus cerverai Zapata Rail. Mustelirallus colombianus Colombian Crake. Mustelirallus erythrops Paint-billed Crake.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The systematic listing follows the order proposed by the American Ornithological Society and its latest supplements (Chesser et al, 2023). Bird endemism is based on the criteria established by Gonzáles-García and Gómez de Silva (2003), where an endemic species (e) is considered to be one that is only found in Mexico; a quasi-endemic (q) is one whose distribution invades no more than 35,000 km 2 into another neighbouring country; a semi-endemic species (s) is considered as such when they are endemic to a country or region during one season of the year.…”
Section: Discussionmentioning
confidence: 99%
“…The systematic listing follows the order proposed by the American Ornithological Society and its latest supplements (Chesser et al, 2023). Bird endemism is based on the criteria established by Gonzáles-García and Gómez de Silva (2003), where an endemic species (e) is considered to be one that is only found in Mexico; a quasi-endemic (q) is one whose distribution invades no more than 35,000 km 2 into another neighbouring country; a semi-endemic species (s) is considered as such when they are endemic to a country or region during one season of the year.…”
Section: Discussionmentioning
confidence: 99%
“…We used the Bird of Panama A Field Guide (Angehr & Dean 2010) to identify the species in the field and evaluate the data of range extension. The American Ornithologist Union checklist was followed to ensure updated scientific names (Chesser et al . 2023).…”
Section: Methodsmentioning
confidence: 99%
“…For each species, we included biological information that we suspected to influence people's awareness on birds, such as color, size, vocal activity, detectability, abundance, daily activity pattern, habitat, and residence status. Moreover, we annotated the bird taxonomic family following Chesser et al (2022). A detailed description of the species biological traits that were used for the study are shown in Table 1.…”
Section: Bird Classification According To Species Biological Traitsmentioning
confidence: 99%